TANGGUNG JAWAB HUKUM DAN PERLINDUNGAN TENAGA PERAWAT DALAM PRAKTIK PELAYANAN KESEHATAN BERBASIS DIGITAL: KAJIAN PUSTAKA ATAS REGULASI DAN ETIKA PROFESI DI INDONESIA - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (Berajah Journal, 2026)
Digital healthcare services in Indonesia have brought about significant changes in nursing practice, whilst also introducing new complexities in legal and professional ethical aspects. This article aims to analyse the legal responsibilities and protections of nurses in the practice of digital healthcare services, as well as to examine the relevance of national regulations and professional nursing ethics in Indonesia. The method used is a normative-analytical approach involving a literature review of laws, government regulations, Ministry of Health regulations, and scientific journals on ethics, nursing law, electronic medical records, telemedicine, and telenursing. The findings indicate that nurses in digital practice remain subject to criminal, civil, and administrative legal liability, whilst legal protection is only afforded if actions comply with professional standards, ethics, standard operating procedures (SOPs), and applicable regulations. On the other hand, professional nursing ethics and digital ethics serve as crucial pillars for nurses in safeguarding patient autonomy, privacy, and data security, as well as limiting the exercise of authority in the digital domain. Consequently, this article emphasises the need for adaptive regulatory strengthening, the development of specific SOPs for digital practice, and a strong integration between legal and professional ethical aspects to ensure the protection of nursing staff whilst maintaining the quality and safety of technology-based healthcare services in Indonesia.